Analisis Infrastruktur Teknologi, Pelatihan Pengajar dan Tantangan dalam Implementasi Model Pembelajaran Literasi Digital untuk Mendukung SDGs 2030 - Sabrina Nur Syifa; Azkya Mumtaz Az-Zahra; Ichsan Fauzi Rachman (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study examines the technical infrastructure, teacher training, and challenges in implementing digital literacy learning models to support the 2030 SDGs. The objective is to analyze how these elements contribute to achieving the SDGs. The methodology employed is a literature review, collecting and analyzing secondary data from various academic sources and policy reports. Findings indicate that integrating technology in education enhances digital literacy and supports the attainment of the SDGs, especially when backed by adequate technological infrastructure and comprehensive teacher training. Challenges include funding limitations, resistance to change, and lack of technical support, particularly in rural areas. The implications of this study emphasize the importance of sustainable investment in educational technology and professional development for teachers to achieve sustainable development goals.